A sonochemical approach to the direct surface functionalization of superparamagnetic iron oxide nanoparticles with (3-aminopropyl)triethoxysilane - Sodipo, Bashiru Kayode; Abdul Aziz, Azlan (Hindawi Publishing Corporation, 2014)
We report a sonochemical method of functionalizing superparamagnetic iron oxide nanoparticles (SPION) with (3-aminopropyl)triethoxysilane (APTES). Mechanical stirring, localized hot spots and other unique conditions generated by an acoustic cavitation (sonochemical) process were found to induce a rapid silanization reaction between SPION and APTES. FTIR, XPS and XRD measurements were used to demonstrate the grafting of APTES on SPION. Compared to what was reported in literature, the results showed that the silanization reaction time was greatly minimized. More importantly, the product displayed superparamagnetic behaviour at room temperature with a more than 20% higher saturation magnetization.